Small farmer's crop protection practices and perceptions in the early 1990s implications for policy and technology development - Rola, A. C. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 1997)
Crop protection practices and perceptions of small farmers were investigated with the aim of identifying technology gaps and policy support to sustainable pest management strategies. The survey covered farmers producing grains (rice and corn), fruits (mango, banana and pineapple), vegetables (cabbage, onion and potato) and tobacco across provinces which are major producers of said crops. Results showed that mango and vegetable farmers are highly dependent on chemical control. Illnesses due to chemicals were reported especially among vegetable farmers. Perceived changes in pest populations before and after pesticide use suggest some semblance of insect resistance. Technology development along with proper management of major pests in mango and vegetables will yield positive social benefits. Policy support to encourage sustainable pest management adoption by farmers could come in the form of setting standards of residue levels, pricing and trade policies, and effective regulation.